Influence of coupling method on the luminescence properties, coupling efficiency, and binding affinity of antibodies labeled with europium(III) chelates - Karsilayan, H; Hemmila, I; Takalo, H; Toivonen, A; Pettersson, K; Lovgren, T; Mukkala, VM (AMER CHEMICAL SOC, 1997)
A series of chelating 4-(phenylethynyl)pyridines having various 1,3,5-triazin-2-ylamino groups at the para position of the phenyl ring was synthesized. Their europium chelates were coupled to antibodies and the properties of antibody conjugates analyzed by fluorometry and in time-resolved fluorometric immunoassay. The substituents in the triazine ring were observed to have various effects on the chelate luminescence, the labeling properties of the chelates, and the immunoreactivity of labeled antibodies. The series of substituted triazinyl derivatives serves as a model of bioreactive groups that can be applied when certain properties are searched for, such as improved chelate solubilities, minimized internal quenching, different effects on the ligand triplet state, and stipulated coupling reactivities.
Keywords: ASSAYS; Biochemistry & Molecular Biology; Chemistry